Creación de un nuevo modelo de negocio para la - Contero, Rodrigo (2010)
We propose trading medium shrimp of 14 grams in Guayaquil with added value shrimp and entire shrimp, both for luxury-class restaurants and hotels. They will receive the product at home. Families will find it in supermarkets in the north of the city. If the customers to buy shrimp with value-added, they will have headless shrimp, peeled, deveined and in portions of pounds, saving time in preparing their meals. The shrimp come packaged with our brand. We will offer 232,500 pounds in the first year on the market. The 67% of the offer will be directing to hotels and restaurants and 23% to families. The companies will buy in lots of 5 pounds, $ 3.10 per pound. The families will get three product lines: a) Integer shrimp at $ 2.40 per pound, b) Heading shrimp at $ 2.80 per pound and c) Added value shrimp at $ 4.20 per pound. If we don´t do the production process called co-packing and distribution, the profitability of the project will be attractive. The NPV required is $ 223,363.37; the IRR is 60%, it is above the MARR 30% of the shrimp sector.